2013
DOI: 10.1007/s00259-012-2323-5
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria predicts silent myocardial ischaemia in type 2 diabetes patients

Abstract: In this group of patients with type 2 diabetes, microalbuminuria was the only predictor of silent ischaemia on MPS. Assessment of microalbuminuria should be routinely considered among the first risk stratification steps for CAD in patients with type 2 diabetes, even though severe ischaemia on MPS is a major predictor of cardiac event-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 57 publications
2
14
0
1
Order By: Relevance
“…The predictive role of an increased BNP-value at baseline is in line with results of a primary prevention study in which BNP was used to identify end organ damage of the heart: in asymptomatic primary prevention patients, BNP screening was able to identify silent heart disease [17]. On the other side and in contrast to several other studies [18,19], neither an increased creatinine level nor the presence of microalbuminuria were independently predictive of an abnormal MPS in the present analysis. This may be explained partly by the frequent use of ACE-/ARB-inhibitors (77%), the highly selected patient group tested and the multiple predictors analysed in the current versus older studies [15,18].…”
Section: Predictors Of An Abnormal Mps In Asymptomatic Diabetic Patientssupporting
confidence: 88%
“…The predictive role of an increased BNP-value at baseline is in line with results of a primary prevention study in which BNP was used to identify end organ damage of the heart: in asymptomatic primary prevention patients, BNP screening was able to identify silent heart disease [17]. On the other side and in contrast to several other studies [18,19], neither an increased creatinine level nor the presence of microalbuminuria were independently predictive of an abnormal MPS in the present analysis. This may be explained partly by the frequent use of ACE-/ARB-inhibitors (77%), the highly selected patient group tested and the multiple predictors analysed in the current versus older studies [15,18].…”
Section: Predictors Of An Abnormal Mps In Asymptomatic Diabetic Patientssupporting
confidence: 88%
“…They recommend screening for male patients in whom the duration of DM is 10 years or even less when more than one cardiovascular risk factor is present. In a recent study by Giovacchini et al, (20) microalbuminuria was the only predictor of silent ischemia in diabetes. Gokcel et al (12) reported a positive correlation between silent ischemia and retinopathy, male sex, hypertension and low HDL-cholesterol levels in patients with DM.…”
Section: Discussionmentioning
confidence: 89%
“…El obtener sobre 10 METS en la PE es buen predictor de ausencia de eventos coronarios en el seguimiento, independiente de otros FRCV e incluso de la presencia de isquemia. 21,22 Respecto a la asociación de IS y presencia de microalbuminuria, también la observamos (en 44%) como otros autores 20 , para quienes aquella fue el único predictor de IS en DM tipo 2. En este estudio sólo el paciente con insuficiencia cardíaca, de los con evento mayor, la presentó.…”
Section: Materials Y Métodosunclassified